Pengaruh Corporate Social Responsibility (CSR) Dan Good Corporate Governance (GCG) Terhadap Return On Equity Perusahaan Jasa Transportasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2015 - Siswanti, Tutik; Carmiat, Carmiat (Feb Universitas Dirgantara Marsekal Suryadarma, 2017)
This study aims to exemine the effect of CSR on ROE, the effect GCG on ROE, and the effect of corporate social responsibility and good corporate governance on ROE. This research is a quantitative study. CSR and GCG as independent variables and ROE as dependent variable. CSR is measured by the standard of the Global Reporting Initiative (GRI), while GCG measured by indicators of institutional ownership, board size, the size of the board of directors, independent directors and audit committee. The sample used in this study presented is a transportation services company listed on the Indonesia Stock Exchange period 2013 to 2015. Data analysis techniques include Normality Test, Linearity, Multiple Linear Regression, Classical Assumption Test : Multicollinearity Test, Test Heteroskidastity, Autocorrelation Test, Hypothesis Testing Partial (t test), Simultaneous Hypothesis Testing (test F) and the Coefficient Determinant. The results uses t test showed that CSR has no effect onÂ Â ROE, GCG effect on ROE, and the results uses F test showed CSR and GCG no effect on ROE. Keywords: CSR, GCG, dan ROE